Oncogene or tumor suppressor gene: An integrated pan-cancer analysis of NBPF1 - Li, Lei; Chen, Sen; Tang, Yueming; Wu, Jie; He, Yangzhige; Qiu, Ling (Frontiers in Endocrinology, 2022)
Abstract Background NBPF1 appears to be a double-edged sword in the carcinogenesis of specific types of tumors, according to current cell-based investigations. However, a systematic pan-cancer analysis is not available thus far, and the significance of NBPF1 in the occurrence and progression of many malignancies is uncertain. method A number of bioinformatics techniques were employed in this study to analyze NBPF1 expression in pan-cancer and investigate the relationship between NBPF1 and clinical characteristics, prognostic outcome, genetic alteration, and tumor immune microenvironment respectively. Furthermore, we explore the possible biological mechanisms of NBPF1 via GO/KEGG and GSEA enrichment analysis. Subsequently, we created an immune risk score (IRS) based upon NBPF1-related immune genes and assessed its value to predict adrenocortical carcinoma (ACC) prognostic outcome and immunotherapy responsiveness. Heterogeneity in immune cell infiltration and antitumor drug sensitivity between the different risk groups were also properly considered. result NBPF1 was shown to be variably expressed in distinct tumor tissues and was also closely relevant to prognosis. Further analysis suggested that NBPF1 seems to be an independent prognostic factor for ACC. In addition, NBPF1 expression was negatively associated with immune cell infiltration in various tumors, notably, NBPF1 may act as an anti-inflammatory factor in the anti-tumor immune response of ACC. Since the immune risk signature based on NBPF1-related immune genes can accurately predict the prognosis of ACC, according to survival analysis. A nomogram integrated clinicopathological features and the immune risk score was also developed for the superior prediction of the prognosis in ACC patients. Furthermore, the level of immune cell infiltration, which is recognized to prevent tumor growth, is higher in the low-risk group of ACC patients. Meanwhile, the high immune risk was accompanied by immunotherapy hyporesponsiveness and lower expressions of certain immune checkpoint genes. In addition, the expression of immune risk signature genes related to the sensitivity of antitumor drugs Nelarabine and Chelerythrine. conclusion NBPF1 could be used as a potential prognostic biomarker for multiple cancers and as well as a key player in the tumor immune microenvironment and tumor immunity. Anti- NBPF1 immunotherapy might be suitable for ACC treatment.